Penerapan Model Pembelajaran Kooperatif Group Investigation Untuk Meningkatkan Kemampuan Membaca Fiksi Siswa Mts Negeri 1 Tuban - Masroin, Masroin (Balai Diklat Keagamaan Surabaya, 2021)
This study aims to describe: (1) the application of the investigative group cooperative learning model can increase student activeness in understanding fictional texts in class IX H MTs Negeri 1 Tuban and (2) the application of the investigative group cooperative learning model can improve students' ability to understand fictional texts. class IX H MTs Negeri 1Tuban. This research is a Classroom Action Research (PTK) which was conducted at MTs Negeri 1 Tuban with the subjects of class IX H students totaling 30 students. Based on the results of the study, it was proven that there was an increase in the quality of learning, namely an increase in student activity and the ability to understand students' fictional texts. The increase in the activity of the learning process was marked by the increase in the activeness of students in the first cycle with a mean value of 85.62 and the mean value in the second cycle of 92.50 compared to the average value before the cycle 66.37. The increase in the ability to read fictional texts was marked by the increase in student learning completeness, namely the mean value in cycle I was 63.1 and the mean value in cycle II was 73.5. The conclusion of this study is that the investigative group cooperative learning model is effectively applied in learning to read fiction texts.